2015
DOI: 10.3390/ijms160816848
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia in Spinal Cord Injury: The Status of Its Use and Open Questions

Abstract: Spinal cord injury (SCI) is a major health problem and is associated with a diversity of neurological symptoms. Pathophysiologically, dysfunction after SCI results from the culmination of tissue damage produced both by the primary insult and a range of secondary injury mechanisms. The application of hypothermia has been demonstrated to be neuroprotective after SCI in both experimental and human studies. The myriad of protective mechanisms of hypothermia include the slowing down of metabolism, decreasing free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 149 publications
(230 reference statements)
0
45
0
2
Order By: Relevance
“…In animal studies, hypothermia decreased basal metabolic rate in the central nervous system, reduced inflammation, apoptosis, excitotoxicity, edema, gliosis, and increased angiogenesis. As well, traumatic SCI models showed improvement with the decreased temperature 30 . A small pilot study in humans with SCI exposed to hypothermia showed a trend towards neurological recovery (43% vs 21%) and no difference in complication rates 31 .…”
Section: Neuroprotectionmentioning
confidence: 80%
“…In animal studies, hypothermia decreased basal metabolic rate in the central nervous system, reduced inflammation, apoptosis, excitotoxicity, edema, gliosis, and increased angiogenesis. As well, traumatic SCI models showed improvement with the decreased temperature 30 . A small pilot study in humans with SCI exposed to hypothermia showed a trend towards neurological recovery (43% vs 21%) and no difference in complication rates 31 .…”
Section: Neuroprotectionmentioning
confidence: 80%
“…Many of these neuroprotective agents have been studied, but without positive results for thoracic spinal cord injury patients [23,24] . Riluzole, a sodium channel blocker, and hypothermia, which decreases central nervous system metabolism, have been shown to be effective neuroprotective agents for the treatment of spinal cord injury [16,[25][26][27] . Mu et al [28] associated riluzole and MPSS in rats with spinal cord injury.…”
Section: Treatmentsmentioning
confidence: 99%
“…Experimental studies as well as clinical experience show that hypothermia can improve the neurological outcome in patients following traumatic and ischaemic brain or SC lesions (Martyrosian et al 2017). The reduction of body temperature divides hypothermia into profound (< 30 °C), moderate (30-32 °C), modest (32-34 °C) and mild (35 °C) (Wang and Pearse 2015). Hypothermia inhibits cellular metabolism by 5-8% per 1 °C, retards basic enzymatic activity, reduces oxygen consumption, and energy demand (Wang and Pearse 2015).…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…The reduction of body temperature divides hypothermia into profound (< 30 °C), moderate (30-32 °C), modest (32-34 °C) and mild (35 °C) (Wang and Pearse 2015). Hypothermia inhibits cellular metabolism by 5-8% per 1 °C, retards basic enzymatic activity, reduces oxygen consumption, and energy demand (Wang and Pearse 2015). Hypothermia increases adenosine triphosphate (ATP) stores, helps to maintain the normal transmembrane ion and neurotransmitter gradients, preserve the BSCB (blood-spinal cord barrier), ameliorate the local oedema, suppress axonal swelling and development of gliosis, reduce oxidative stress, inflammation, and mitochondrial membrane permeabilization which is the point-of-no-return in apoptosis (Alkabie and Boileau 2016).…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%